Survey and Characterization of Fusarium oxysporum f. sp. cubense Associated with Fusarium Wilt of Banana in Major Growing Regions of Tamil Nadu, India - , Vanitha A, Kannan C (Archives of Current Research International, 2025)
The survey-based experimental study was conducted from July 2023 to May 2024 at the Department of Plant Pathology, Faculty of Agriculture, Annamalai University, Tamil Nadu, and in banana fields across major banana-growing regions of the state. Surveys were carried out in twenty locations covering six districts, representing AAA, AAB, ABB, and AB genome groups under different soil types. Infected pseudostem tissues were surface-sterilized and cultured on potato dextrose agar medium, and the resulting isolates were characterized based on colony morphology and conidial dimensions of macroconidia, microconidia, and chlamydospores. Genomic DNA was extracted using the CTAB method, and the ITS region was amplified with universal primers ITS4/5, sequenced, and analyzed through BLAST and phylogenetic inference in MEGA 7. A total of twenty morphologically distinct isolates were obtained, and their cultural and conidial features were documented. The BLAST search confirmed the identity of the isolates as Fusarium oxysporum and Fusarium oxysporum f. sp. cubense with an amplicon size of 500 bp. The study revealed that banana cultivation in Tamil Nadu was severely affected by Fusarium oxysporum f. sp. cubense, thereby highlighting the urgent need for region-specific disease management strategies, particularly the identification and promotion of resistant cultivars. Furthermore, continuous molecular surveillance and pathogen monitoring were considered essential for detecting the emergence of highly virulent strains and for ensuring sustainable banana production in the region.